A Comprehensive Approach to Posttraumatic Lymphedema Surgical Treatment - Nicolás Pereira; Vanessa Oñate; Ricardo Roa (Archives of Plastic Surgery, 2023)
Background Posttraumatic lymphedema (PTL) is sparsely described in the literature. The aim of this study is to propose a comprehensive approach for prevention and treatment of PTL using lymphovenous anastomosis (LVA) and lymphatic vessels free flap, reporting our experience in the management of early-stage lymphedema.